The Early Marginalists and the Transformation of Distribution Theory - Baum, S. (Journal of Income Distribution®, 1992)
This paper examines the roles of Jevons, Menger and Walras in transforming distribution theory from the analysis of a social issue into a subset of general price theory. The relegation of social and distributional questions to a separate, overtly normative branch of study, combined with abstract theoretical support for the optimality of market systems, in a long-term derailment of the socio-economic analysis of distribution. The work of the early marginalists had the unintended result of setting an influential precedent for the removal of distribution theory from its social and historical context.